Transforming Ta’dib into Practice: A Conceptual Human Resource Management Model for Islamic Religious Education Teachers - Muhammad Rifai Lubis; Muhammad Abzar Duraesa; Noorthaibah Noorthaibah; Nafi'ah Rohmadini (JURNAL AL-TANZIM, 2026)
This study aims to develop a human resource management model based on ta’dib for Islamic Religious Education teachers in the Smart Society 5.0 era. This study is motivated by the tendency in teacher management within Islamic educational institutions to continue emphasising administrative, technical, and performance aspects while giving inadequate attention to the moral, intellectual, and spiritual formation of teachers. This study employs a qualitative library research design, including document analysis, content analysis, and conceptual synthesis. Primary data are sourced from the works of Syed Muhammad Naquib al-Attas on ta’dib, adab, science, Islamic education, and the Islamic outlook on life. In contrast, secondary data are obtained from relevant studies on Islamic education management, human resource management, teacher competency, artificial intelligence, and Smart Society 5.0. The results of the study indicate that ta’dib-based human resource management can be structured around five interrelated dimensions: value-oriented teacher recruitment, adab-centred professional development, ethical performance evaluation, knowledge-based organisational culture, and humanistic digital adaptation. The novelty of this study lies in the transformation of ta’dib from a philosophical concept in Islamic education into a conceptual framework for the management of Islamic Religious Education teachers. The implications of this research emphasise that Islamic educational institutions need to manage teachers not only as instructional staff, but also as professional, ethical, spiritual, and digital-humanistic mu'addib figures.